THE LANGUAGE OF INCLUSION: CODE-SWITCHING IN POLITICAL CAMPAIGNS - Xushvaqtova Mohira (TADQIQOTLAR, 2025)
Annotation.  This  article  examines  the  role  of  code-switching  in  political campaigns through a linguistic and sociolinguistic lens. Politicians who aim to connect with  multilingual  and  multicultural  audiences  often  alternate  between  languages during their speeches. This research identifies the rhetorical and symbolic functions of such switches and emphasizes how they contribute to the creation of inclusive political discourse. The methodology consists of a qualitative discourse analysis of speeches that  were  delivered  by  multilingual  politicians.  The  findings  indicate  that  code-switching  functions  as  a  tool  for  audience  alignment,  identity  representation,  and emotional  emphasis.  The  study  concludes  that  when  code-switching  is  used authentically,  it  strengthens  political  engagement  and  fosters  inclusivity  among linguistically diverse voters.